Some reproduction aspects of Ephestia kuehniella Zeller (Lepidoptera, Pyralidae) under mass rearing conditions - Falp, Lluis (2011)
Submitted by João Tavares (tavares@uac.pt) on 2010-12-15T12:27:16Z No. of bitstreams: 1 Some reproduction aspects of Ephestia kuehniella Zeller under mass rearing conditions.pdf: 3754877 bytes, checksum: 261c14cb41735946ca9105558b1e5b64 (MD5)